Beyond "Points of Control": logics of digital governmentality - Romain Badouard; Clément Mabi; Guillaume Sire (Internet Policy Review, 2016)
In this paper, we aim to show the heuristic benefit of Michel Foucault's concept of "governmentality", in order to describe three logics of power and control within digital environments. These three logics – directing, constraining and framing online behaviours – are similar to Foucault's approach to power, which is understood as a means to "lead other people's behaviours", as it is in this case enacted through the mediation of technical resources, such as software, algorithms and operating systems. This paper provides three illustrations of these logics of governmentality: the way in which Google tries to direct webmasters' practices with the help of its SEO guidelines and a webmaster ranking system (governmentality by incentives); the way by which developers constrain online behaviours through websites and software (governmentality by design); the way Apple frames the work of app developers in order to institute specific standards for action and interaction within its iPhone operating system (governmentality by framing).
Keywords: 300; Governmentality; Framing; User behaviour